Cutting through Syria’s Silence: Trauma in Khalid Khalifa’s "No Knives in the Kitchens of this City" and Asaad Almohammad’s "An Ishmael of Syria" - Dagamseh, Abdullah M.; Al-Taweel, Muna; Barker, Jamie (The international journal of literary humanities, 2021)
This study traces trauma in Syrian literary narratives where it is otherwise unspoken or ambiguous. It identifies trauma within the structural presentation of two novels by two contemporary Syrian writers: Khalid Khalifa’s “No Knives in the Kitchens of this City” and Asaad Almohammad’s “An Ishmael of Syria.” We focus on these two Syrian novels in particular because, when read together, they offer a timeline of life in Syria from 1960s well into the 2010s, after the Syrian civil war. We do a textual analysis of both texts by relying on the literary trauma theories of Cathy Caruth and Joshua Pederson. We interpret the lack of chronology and the shifts in narrative perspective in both texts as evidence of trauma that cannot be explicitly expressed otherwise. In fact, rarely did Syrian literature explicitly express the traumatic symptoms that Syrians were living with. This is why the focus of this study is on the structure of the texts rather than the events of the narratives themselves. The characters never discuss their behavior or their feelings within a context of trauma; however, the fragmentation seen in the presentation of the texts echoes the trauma underlying the events within the plots.